The Cultural Environment of International Business / Third Edition - David Kenneth; Terpstra Vern (South-Western, 1991)
The Basics of Culture, Prologue: The Challenge of International Business in the 1990s, Culture, Language, Culture and the Shaping of Human Motivation, Education, Religion, Values, The Social Organization of Human Behavior, Technology, Social Organization, Political Environment, Environments and Issues, Classification of Countries by Economic Performance, Bibliography, Index.